Arsenic health risks and interaction with salinity in coastal areas of Bangladesh - Tawhidul, Islam Md; Asma, Khatun Mst.; Islam, Moinul; Kotani, Koji (Frontiers in Public Health, 2025)
BackgroundArsenic contamination poses significant health risks to inhabitants in coastal areas. However, little is known about the health risks associated with the interaction of arsenic with salinity. This study aims to examine how the morbidities from water-related diseases (WRD) and cardiovascular diseases (CVD) are associated with arsenic contamination under salinity with multiple water sources and uses as well as how such risks can be reduced. It is hypothesized that WRD and/or CVD morbidity rates worsen when severe arsenic contamination comes with salinity, and there exist effective countermeasures for the risk reduction by different channels.MethodsWe collected data from 689 households using questionnaire surveys on diseases, water uses, safety measures and sociodemographic factors from arsenic areas under salinity in Bangladesh and employed logit and ordered probit regression models to analyze the incidence and intensity of the morbidity.ResultsThe results reveal that, first, households in high arsenic contaminated areas have higher morbidity rates of WRD and/or CVD than those in no arsenic contaminated areas under salinity. Second, the daily use of washing and cooking water (drinking water) increases (does not increase) the probability of WRD and CVD morbidities, respectively. Third, households using deep tubewells as a safety measure face greater WRD morbidity than those using rainwater.ConclusionThe results suggest that cooking and washing are the main channels for increasing the health risks and two countermeasures are recommended: (i) extensive year-round uses of rainwater and (ii) adoption of regularly tested water sources, such as groundwater, even for cooking and washing to reduce the risks for achieving Sustainable Development Goal 3.